Social comparison and performance: Experimental evidence on the fair-wage effort hypothesis - Simon Gächter; Christian Thöni (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2009)
We investigate the impact of wage comparisons for worker productivity. We present three studies which all use three-person gift-exchange experiments. Consistent with Akerlof and Yellen's (1990) fair wage-effort hypothesis we find that disadvantageous wage discrimination leads to lower efforts while advantageous wage discrimination does not increase efforts on average. Two studies allow us to measure wage comparison effects at the individual level. We observe strongly heterogeneous wage comparison effects. We also find that reactions to wage discrimination can be attributed to the underlying intentions of discrimination rather than to payoff consequences.
Keywords: J31; J71; C91; C92; 330; fair wage-effort hypothesis; wage comparison; gift exchange; horizontal fairness; discrimination; Lohn; Gerechtigkeit; Soziale Beziehungen; Leistungsmotivation; Arbeitsproduktivität; Austauschtheorie (Soziologie); Test